Erasures and invisibilities: technical images, surveillance, violence and resistance - Del Valle-Ferreto, Luis Alberto (2025)
This article examines the role of surveillance images, exploring how technologies of control produce both surveillance and erasure, and simultaneously configure subjectivity and exclusion. Such operative images not only document but also configure a ubiquitous regime of visuality, and their production invisibilizes both the subjects and the structures of violence that produce them. However, technical images, although designed for surveillance and control, can be reappropriated and reinterpreted as vestiges, ashes or traces of erased alterities: fragments that allow us to reconstruct histories of exclusion and power. This article proposes that these images can become archives of violence and resistance, whose traces can be recovered in an aesthetic and political key. Finally, the paper analyzes some possible strategies of subversion that reveal the tension between surveillance and resistance in the contemporary context of technical image production.